Environmental Education as a Tool for Sustainability: Practices and Challenges - Siqueira, Cláudio Alves; Alencar, Janaina Kawata de (Scientific Journal ANAP, 2025)
Objective: This paper addresses environmental education as an essential tool for promoting sustainability in different social contexts.Methodology: Based on a literature review, the study explores the role of environmental practices in the development of critical awareness and transformative actions.Originality/relevance: In addition, the main challenges in the implementation of environmental education programs and projects are analyzed, highlighting the importance of integrating theory and practice.Results: The results indicate that, despite significant advances, there is a need for greater political, pedagogical and community engagement to consolidate environmental education as a pillar of sustainability.Theoretical/methodological contributions: The study offers a comprehensive review of environmental education as an essential pillar for promoting sustainability, highlighting the need for integration between theory and practice, highlighting the importance of interdisciplinary and participatory methodologies in teaching sustainability.Social and environmental contributions: The work highlights environmental education as an instrument to form critical citizens engaged in environmental preservation, discussing the implementation of projects such as community gardens, composting systems and awareness campaigns on reducing consumption.
Keywords: Environmental education; sustainability; environmental practices; challenges; critical awareness